Structural analysis principles, methods and modelling - Ranzi, Gianluca; Gilbert, R. I. (CRC Press, 2015)
Combining a user-friendly, practical approach with detailed derivations and mathematical background, this text shows students how to use structural analysis accurately and efficiently to solve engineering problems.